KEGIATAN PENYULUHAN FISIOTERAPI TENTANG OSTEO ARTHRITIS KNEE DI RUMAH SAKIT PARU DUNGUS - Mahiza Rahmayani; Kristiyono Putro; Nungki Marlian Yuliadarwati (LPPM Universitas Abdurrab, 2023)
Dungus Regional General Hospital is one of the hospitals located in the city of Madiun. Patients who visit the hospital, especially in the physiotherapy clinic, are mostly elderly. As we know, a degenerative process will make a person experience a setback, especially in physical function, one of which is musculoskeletal problems such as knee osteoarthritis (knee pain). With this case, counseling about knee osteoarthritis was carried out aiming to find out what is meant by knee osteoarthritis, what are the signs when exposed to knee osteoarthritis and how to treat it at home to reduce the pain experienced. The method used is by providing counseling to the community, in the form of health promotion about knee osteoarthritis, by using leaflets as a medium, to facilitate public understanding, conducting useful debriefing to gather information about complaints experienced by the community, and educating with exercises and handling that can be done at home to reduce complaints. The counseling process went smoothly, the community began to understand the exercises they had been taught to do at home, with the aim of getting people's understanding from 0% to 100% after the counseling was carried out. So that there is a decrease in the level of pain experienced by the community after doing exercises at home. With the counseling activities carried out to the community, it can increase people's knowledge about knee osteoarthritis, how to treat it at home and can reduce the pain experienced.